Should I Stay or Should I Go? Revisiting Influencing Factors of SPED Teacher Attrition & Retention: A Review of the Literature - Theoharis, Raschelle; Fitzpatrick, Michael (Journal of the American Academy of Special Education Professionals, 2013)
Evidence continually reports that special education (SPED) teachers stay in the field three-to-five academic school years before leaving the profession. A systematic review of historical-to-current literature revealed that personal, employment, and external factors were the three most prevalent variables that influenced attrition and retention (A&R) rates of SPED teachers. Although A&R has significant implications for student learning outcomes, the focus of this article is on analyzing these casual factors in an attempt to revisit and revitalize this important issue.